Tari Lemang dan Komunikasi Lintas Budaya: Sebuah Pemaknaan di Kota Tebing Tinggi - Go Meylisa; Zuhriah Zuhriah; Hasan Sazali (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
As multicultural societies continue to experience increasing cultural interaction, understanding how traditional performing arts function as media of intercultural communication has become an important scholarly concern. This study examines the meaning of Lemang Dance from the perspective of cross-cultural communication in Tebing Tinggi City to explore how the performance represents cultural identity while facilitating communication among diverse ethnic communities. A qualitative descriptive approach was employed through participant observation, in-depth interviews, and documentation. The findings reveal that Lemang Dance embodies the community’s collective identity and conveys nonverbal messages through movements, facial expressions, costumes, and musical accompaniment that symbolize mutual cooperation, harmony, and togetherness. The performance is widely understood and appreciated by different ethnic groups, demonstrating its role as an effective medium of cross-cultural communication. The novelty of this study lies in positioning Lemang Dance as a traditional performing art that functions simultaneously as a cultural identity marker and an intercultural communication medium within a multicultural society. The findings contribute to the advancement of cultural communication studies and provide practical insights for preserving local cultural heritage while strengthening intercultural understanding through traditional performing arts.